Improvements in quality of life of patients with multiple sclerosis receiving alemtuzumab in clinical practice: the LEMVIDA study - José Eustasio Meca-Lallana; Sara Eichau; Bonaventura Casanova; Elena Álvarez Rodríguez; Antonio Pato; Mireia Forner; Baldo Toledo (Journal of Patient-Reported Outcomes)
Abstract Background Alemtuzumab is a humanized monoclonal antibody approved for the treatment of relapsing-remitting multiple sclerosis (RRMS). Its efficacy and safety have been widely demonstrated in clinical trials, but experience from real-world cohorts is also needed to support its clinical use. Quality of life (QoL) outcomes are an important complement to the clinical benefits of treatment, offering a patient-centered perspective on how the drug contributes to general well-being. In this line we aimed to evaluate the QoL of patients treated with alemtuzumab in clinical practice. Methods This prospective 3-year multicenter study was carried out in adult patients diagnosed with RRMS who had started alemtuzumab according to clinical practice within 8 weeks before inclusion. The primary endpoint was the change in QoL over three years of treatment with alemtuzumab using the 29-item Multiple Sclerosis Impact Scale (MSIS-29). Secondary endpoints included changes from baseline in the 21-item Modified Fatigue Impact Scale (MFIS-21), Beck Depression Inventory (BDI-II), Symbol Digit Modalities Test (SDMT, oral version) and Work Productivity. Disability worsening was also assessed based on the Expanded Disability Status Scale (EDSS), along with the annualized relapse rate (ARR) and radiological activity. Results A cohort of 165 patients was analyzed (mean age 38.6 years, mean disease duration 8.5 years, mean EDSS score 3.3). MSIS-29 physical domain scores decreased significantly from baseline by a mean of 7.2 ± 1.8 points at year 1, 6.4 ± 2.2 at year 2 and 5.6 ± 2.3 at year 3 (p < 0.05 in all cases). Similarly, MSIS-29 psychological domain scores decreased significantly by a mean of 7.9 ± 2.4 points at year 1, 12.8 ± 2.9 at year 2 and 13.2 ± 3.0 at year 3 (p < 0.05 in all cases). Significant reductions from baseline were also evidenced in MFIS-21 and BDI-II scores, while SDMT scores remained unchanged. During the 3 years on alemtuzumab, the ARR was 0.15, representing an 83% reduction from the 2 years before initiation. At 3 years, 81.5% of patients were free from radiological activity and 87% were free from disability worsening. Conclusions These results indicate early and substantial improvements in patients’ perception of their QoL and functioning with alemtuzumab that were sustained over three years.